Humanitarian Crisis on The Dynamics of The Russia-Ukraine Conflict (Analysis of Humanitarian Law and Proposals for the Strengthening of the International Court) - Yudi Rianto Ratu; Ernesta A. Brahmana; Tarsisius Susilo; Sarwo Supriyo; Thomas HK. Sinaga (International Journal Labs, 2025)
This study examines international humanitarian law in the dynamics of the Russia-Ukraine conflict, which has had a significant impact on the humanitarian crisis in Ukraine. The background of this study focuses on the existing fact that the Russian military invasion since February 2022 has caused the largest humanitarian crisis on the European continent. The Russia-Ukraine conflict has resulted in casualties, war injuries, infrastructure damage, and the absence of basic rights such as health care and access to basic necessities. Millions of Ukrainians have fled, both to neighboring countries and within Ukraine to safer locations. The purpose of this study is to analyze the application of international humanitarian law in responding to the Russia-Ukraine conflict and to provide recommendations for the development of more relevant policies in this context. The method used in this study is a qualitative approach through the analysis of legal documents and case studies, with a focus on the humanitarian crisis caused by the dynamics of the Russia-Ukraine conflict since February 2022. This analysis reveals that the principles of international humanitarian law are not fully applied in the context of the Russia-Ukraine conflict. The research findings show that the humanitarian crisis in this conflict is quite concerning and requires UN intervention. Based on these findings, this study recommends that the UN urge Russia to implement a ceasefire with Ukraine and to ensure the realization of international humanitarian law protection in humanitarian corridors based on international agreements and supervised by the UN, in order to evacuate civilians and distribute humanitarian aid.